The Takhassus Qur'an Memorization Program: A Strategy for Shaping a Qur'anic Generation (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Memorizing the Qur'an is a religious tradition with significant impacts on character formation and spiritual intelligence. This study examines the implementation of the takhassus memorization program at SMP IT Ikhlas Cendekia Lahat, focusing on its strategies and challenges. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and document analysis from 13 students aged 13–14 years. The program's structured daily schedule, incorporating murojaah, talaqqi, and memorization sessions, proved effective in improving students' memorization skills. Results showed a reduction in average memorization time from 10 to 3 minutes per page, with enhanced accuracy in tajwid and makharijul huruf. Additionally, the program fostered discipline and responsibility among students. However, challenges included diverse learning capabilities, limited time for individualized guidance, and the need for more intensive teacher training. These findings highlight the potential of the takhassus program in general schools and its role in fostering Qur'anic generations. Further research is recommended to explore the integration of technology in similar programs to optimize efficiency and learning outcomes.